SEED GERMINATION OF Pouteria torta (MART.) RADLK. SUBESP. torta IN DIFFERENT ENVIRONMENTAL CONDITIONS - Oliveira, Ademir Kleber Morbeck; Pina, Jose Carlos (Floresta, 2019)
Germination is considered a critical step in the seedling production process aiming the recovery of environments. Thus, understanding the germination behavior of native species with potential for economic use contributes to the development of the forest seed and seedling chain. Considering the limited information on the tree species Pouteria torta subesp. torta, this study aimed to evaluate its seed germination and formation of normal seedlings using different temperatures and substrates. The experiment was conducted in germination chamber in a research laboratory using two substrates (paper and vermiculite) and six temperatures (20, 25, 30, 35, 20-30 and 25-35 °C) in a completely randomized design in a 2x6 factorial arrangement. Daily evaluation was conducted to verify primary root emission, seed vigor, and seedling formation. The results indicated that the primary root protrusion process began after 20 days of testing under the best conditions, with germination time lasting longer than two months. The results obtained also showed that there was interaction between factors, with use of the vermiculite substrate and the temperatures of 35 and 25-35 °C producing the best germination rates and germination speed index, and use of the paper substrate and the temperatures of 30 and 35 °C showing the best mean germination time. Considering the analyzed variables (germination, germination speed index, and formation of normal seedlings), the temperatures of 35 and 25-35 °C and the vermiculite substrate are the most suitable for the production of Pouteria torta subesp. torta seedlings.